Functional fermented meat products with probiotics—A review - Munekata, Paulo E. S.; Pateiro, Mirian; Tomasevic, Igor; Domínguez, Rubén; da Silva Barretto, Andrea C. [UNESP]; Santos, Eva M.; Lorenzo, José M. (Oxford University Press (OUP), 2021)
Fermentation has been an important strategy in the preservation of foods. The use of starter cultures with probiotic activity has gained the attention of researchers to produce functional fermented meat products. This review aims to overview the main strengths, weakness, opportunities and threats of fermented meat products with probiotics. Fermented meat products can be considered as a relevant matrix for the delivery of probiotics with potential health benefits. Moreover, fermented meat products produced by traditional methods are sources of probiotics that can be explored in the production of functional meat products. However, some barriers are limit the progression with these products: the complex selection process to obtain new and tailored probiotic strains, the current perception of healthiness associated with meat and meat products, and the limited application of probiotic to fermented sausages. Promising opportunities to improve the value of functional fermented meat products have been developed by exploring new meat products as functional fermented foods, improving the protection of probiotics with microencapsulation and improving the quality of meat product (reducing nitrate and nitrate salts, adding dietary fibre, and exploring the inherent antioxidant and cardioprotective activity of meat products). Attention to potential threats is also indicated such as the unclear future changes in meat and meat products consumption due to changes in consumer preferences and the presence of competitors (dairy, fruit and vegetable-based products, for instance) in more advanced stages of development and commercialization. Significance and Impact of Study: This review provides an overview of the Strengths, Weakness, Opportunities and Threats related to the development of functional fermented meat products with probiotics. Internal and external factors that explain the current scenario and strategies to advance the production are highlighted.
Keywords: autochthonous probiotics; health benefits; healthier meat products; microencapsulation; probiotics; sausages; starter cultures